Overweight and obesity among elderly in an urban slum of Puducherry: A facility-based descriptive study - Bijaya Nanda Naik; Sitanshu Sekhar Kar; Marie Gilbert Majella; Daivanai Sundaram Nachiappan (Wolters Kluwer Medknow Publications, 2018)
Background: Overweight and obesity are important addendum to the pool of risk factors for noncommunicable disease (NCD) among the elderly. Objectives: The objectives of this study were to find (1) the proportion of overweight and obesity and (2) the distribution of overweight and obesity based on sociodemographic characteristics and four major risk factors for NCDs (smoking, alcohol consumption, unhealthy diet, and physical inactivity) among the elderly attending the out-patient department/NCD clinic of a Urban Health and Training Centre (UHTC). Materials and Methods: This facility-based descriptive study was conducted among 181 elderly attending one UHTC, in Puducherry during June and July 2015. A pretested interview schedule was used to obtain information on sociodemographic details and history of NCD risk factors after obtaining verbal informed consent. Anthropometric measurements were taken as per standard procedures prescribed by the World Health Organization. Body mass index (BMI) was calculated and classified using BMI classification for the Asian population. Results: Among the elderly, 18% were overweight and 51% were obese. The proportion of obesity was more among females than males. Obesity was found to be decreasing with increase in age. Overweight and obesity were found to be significantly inversely related to chronic disease status. Overweight and obesity were proportionately more among elderly who were consuming alcohol and doing less physical activity than prescribes. However, the proportion of overweight/obees elderly with no tobacco use and not having unhealthy diet was found to be more than their counterpart. Conclusion: Overweight and obesity are important public health problems in the study population. Hence, interventions should be implemented targeting elderly as well as the adult to decrease the obesity and overweight among the elderly.